Adam Watkins' First Day at Kindergarten - Watkins, Howard::::::::: (1983)
Class photograph all standing: Adam Watkins in middle wearing rainbow shirt, Art Wille to his right, Heather Docker in sun dress with red straps; Devon Bleile-Kratzer in back in front of big apple; teacher standing in back